2010
DOI: 10.1590/s1807-59322010001200014
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of phosphodiesterase type 5 inhibitor on serum oxidative status and prolidase activities in men with erectile dysfunction

Abstract: OBJECTIVES:To investigate the acute effect of phosphodiesterase type 5 (PDE5) inhibitor on erectile dysfunction by evaluating serum oxidative status and prolidase activity.METHODS:Serum samples of 36 patients with erectile dysfunction and 30 control cases were analyzed for total antioxidant status, total oxidant status, and prolidase activity, before and after the administration of tadalafil citrate.RESULTS:Before and after tadalafil citrate administration, serum total antioxidant status, total oxidant status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
11
0
3
Order By: Relevance
“…Ozgur et al 68 reported that udenafil decreased the MDA level in ischemia-reperfusion injury caused by rat testicular torsion/detorsion. Savas¸et al 69 reported that tadalafil decreased the total oxidant status (TOS) and increased the total antioxidant status (TAS) in men with erectile dysfunction. In the present study, we determined the MDA levels in our groups, and our results were similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ozgur et al 68 reported that udenafil decreased the MDA level in ischemia-reperfusion injury caused by rat testicular torsion/detorsion. Savas¸et al 69 reported that tadalafil decreased the total oxidant status (TOS) and increased the total antioxidant status (TAS) in men with erectile dysfunction. In the present study, we determined the MDA levels in our groups, and our results were similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Prolidase activity has been shown in plasma erythrocytes, leucocytes, and fibroblasts and in organs like the kidney, the brain, the heart, the liver, the small intestines, the stomach, the lung, the spleen, the thymus, and the uterus [19]. While a higher prolidase activity is observed in patients with osteoporosis, osteoarthritis, hypertension, coronary artery disease, and erectile dysfunction [8, 9, 17, 18, 20, 21], a lower level is observed in renal insufficiency because the main source of prolidase is the kidney [19]. The severity of the antioxidant stress is directly correlated with the inhibition of collagen production in which prolidase is the main enzyme [19].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of prolidase seem to be associated with increased levels of nitric oxide and oxidative stress along with decreased levels of antioxidant [7]. Also studies on vasculogenic erectile dysfunction have detected higher serum levels of prolidase [8, 9]. In this study we aimed to examine the effect of hCG on prolidase activity, oxidative stress, and levels of antioxidant enzyme in the testicles and penile tissue in a rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Hücrede cGMP (siklik guanozin monofosfat) yıkımını engelleyen ve stoplazmik cGMP konsantrasyonunu arttırarak etkisini göste-ren bu grup ilaçların anti-oksidan etkilerini gösteren çalışmalar da vardır (14)(15)(16)(17)(18)(19)(20)(21)(22). Farklı dozlarda ve farklı sürelerde uygulanan PDE5 inhibitörlerinin; diyabet (14,15), iskemi-reperfüzyon (16)(17)(18), pulmoner hipertansiyon (19,20) ve kardiyomiyopati (21) gibi deneysel modellerde kalp, böbrek, over ve kavernöz dokularda oksidatif stresi azaltıp fonksiyonel iyileşme sağladığı gösterilmiştir.…”
Section: Introductionunclassified
“…Farklı dozlarda ve farklı sürelerde uygulanan PDE5 inhibitörlerinin; diyabet (14,15), iskemi-reperfüzyon (16)(17)(18), pulmoner hipertansiyon (19,20) ve kardiyomiyopati (21) gibi deneysel modellerde kalp, böbrek, over ve kavernöz dokularda oksidatif stresi azaltıp fonksiyonel iyileşme sağladığı gösterilmiştir. Bunun yanı sıra erektil disfonksiyonlu hastalarda PDE5 inhibitör-lerinin akut olarak serum oksidatif stres düzeyini azalttığı bildirilmiştir (22).…”
Section: Introductionunclassified